The protective effect of letrozole in a rat ovarian ischemia-reperfusion injury model - Şener Gezer; Mustafa Başaran (Van Tıp Dergisi, 2020)
INTRODUCTION: Torsion of the ovary is a surgical emergency. Future fertility is an important question for choosing the most appropriate treatment strategy as radical or conservative. Conservative treatment includes detorsion of the twisted ovary and after detorsion, the ischemic injury in ovary increases with reperfusion. During the detorsion process, abundant amounts of reactive oxygen species (ROS) are produced. ROS causes cellular injury by attacking cellular membranes through the peroxidation of polyunsaturated fatty acids and causing cellular death. Letrozole is a nonsteroid aromatase inhibitor that blocks estrogen production in all tissues, increases gonadotropin secretion and induces follicular development. METHODS: In this study, rats are divided into 5 groups including 8 rats in each group; control group, ischemia group, ischemia and letrozole group, ischemia-reperfusion group, ischemia-reperfusion and letrozole group. For each group Malondialdehyde (MDA) levels were measured, degree of ischemia and number of follicles were recorded by histopathological examination. Endometrial thicknesses were also measured. RESULTS: In the ischemia and ischemia-reperfusion groups, MDA levels and grade of ischemia were significantly decreased with letrozole. Ovarian follicle numbers were higher and endometrial thickness was lower in the letrozole used groups. DISCUSSION AND CONCLUSION: Letrozole can be protective on ovarian ischemia-reperfusion injury and this effect will be related to hypoestrogenic environment by inhibition of aromatase activity, antiinflammatory effects and increased blood flow to the ovary by letrozole.